IMPACT OF CORPORATE GOVERNANCE ON THE FINANCIAL PERFORMANCE OF ISLAMIC BANKS IN PAKISTAN - Ali Shah, Taimoor; Shehzad, Dr. Naveed; Ahmad, Umair; Mehmood, Wajid (The journal of contemporary issues in business and government, 2022)
The objective of the study was to examine the impact of corporate governance on the financial performance of Islamic banks working in Pakistan. The population of the study was Islamic banks working in Pakistan and seven (7) Banks were selected as a sample size through simple random sampling technique. The dependent variable was return on assets while independent variables were board size, female director, age of experience, firm size and productivity. Data was collected from the annual reports of Islamic banks websites for the year 2017 to 2021. Panel Diagnostic Test, regression analysis and correlation matrix were used for analysis. Results reflect that firm size, board size and productivity were found positively significant. Whileageof experience was inversely significant and female director was found statistically insignificant. The magnitude of firm size was high as compared to other significant variables. However, female director was found insignificant so it has no impact on return on assets.